Historical dictionary from the Great War to the Great Depression - Wynn, Neil A. (Historical dictionaries of U.S. history and politics., 2014)
This second edition of Historical Dictionary from the Great War to the Great Depression covers the history of this period through a chronology, an introductory essay, appendixes, and an extensive bibliography. The dictionary section has more than 700 cross-referenced entries on important personalities, politics, economy, foreign relations, religion, and culture. This book is an excellent access point for students, researchers, and anyone wanting to know more about a vital period in U.S. history.